Economic Crisis and Personal Financing in Nigeria - Akinyede, Oyinlola Morounfoluwa; Ayodele, Thomas Duro; Olasupo, Sunday Festus (Archives of Business Research, 2022)
The study was carried out to find out the relationship between economic crisis and personal financing among Nigerian workers. The research work made use of both primary and secondary data. Primary data were collected through questionnaires and secondary data sourced from the Central Bank Annual Reports and Bureau of Statistics. Multivariate analysis was applied to determine the relationship between Economic crisis (proxied by inflation, exchange rate, unemployment and cost of living) and personal financing (proxied by spending, tax, savings and investment). Results from the analysis showed a significant positive relationship between economic crisis and personal savings of Nigerian workers. The results showed further that both workers’ personal spending and taxes have a positive relationship with the economic crisis in Nigeria, and their relationships are statistically significant at a 5% significance level. It means all the proxied economic crisis variables jointly affect Nigerian workers’ personal savings, spending and personal taxes. However, economic crisis had no significant effect on the investment of Nigerian workers. Economic crisis does not influence how Nigerian workers invest their meagre income. Therefore, the economic drivers (governments) are advised to pay more attention to tackling the problems of the high exchange rate, inflation rate, and unemployment rate bedeviling the country to reduce the overall cost of living in Nigeria.